Telephone triage in general practices: A written case scenario study in the Netherlands. (2nd January 2016) - Smits, Marleen; Hanssen, Suzan; Huibers, Linda; Giesen, Paul
Abstract: Objective : General practices increasingly use telephone triage to manage patient flows. During triage, the urgency of the call and required type of care are determined. This study examined the organization and adequacy of telephone triage in general practices in the Netherlands.Design : Cross-sectional observational study using a web-based survey among practice assistants including questions on background characteristics and triage organization. Furthermore, practice assistants were asked to assess the required type of care of written case scenarios with varying health problems and levels of urgency. To determine the adequacy of the assessments, a comparison with a reference standard was made. In addition, the association between background characteristics and triage organization and the adequacy of triage was examined.Setting : Daytime general practices.Subjects : Practice assistants.Main outcome measures : Over- and under-estimation, sensitivity, specificity.Results : The response rate was 41.1% (n = 973). The required care was assessed adequately in 63.6% of cases, was over-estimated in 19.3%, and under-estimated in 17.1%. The sensitivity of identifying patients with a highly urgent problem was 76.7% and the specificity was 94.0%. The adequacy of the assessments of the required care was higher for more experienced assistants and assistants with fixed daily work meetings with the GP. Triage training, use of a triage tool, and authorization of advice were not associated with adequacy of triage.Conclusion : Triage by practice assistants in general practices is efficient (high specificity), but potentially unsafe in highly urgent cases (suboptimal sensitivity). It is important to train practice assistants in identifying highly urgent cases. Key points: General practices increasingly use telephone triage to manage patient flows, but little is known about the organization and adequacy of triage in daytime practices. Telephone triage by general practice assistants is efficient, but potentially unsafe in highly urgent cases. The adequacy of triage is higher for more experienced assistants and assistants with fixed daily work meetings with the general practitioner.